Biallelic versus Monoallelic TP53 Inactivation in Hematologic Malignancies: A Comparative Meta-Analysis of Lymphoid and Plasma Cell Disorders - Atika Indah Sari (HM Publisher, 2026)
Background: The tumor suppressor protein p53, encoded by the TP53 gene on chromosome 17p13.1, functions as the central guardian of genomic stability. In hematologic malignancies, including multiple myeloma (MM), chronic lymphocytic leukemia (CLL), and myelodysplastic syndromes (MDS), p53 dysfunction acts as a universal marker of chemoresistance and disease progression. Current clinical staging systems frequently conflate chromosomal deletion, or del(17p), with somatic mutation, thereby failing to distinguish between monoallelic (single-hit) and biallelic (double-hit) inactivation. This lack of granularity obscures the distinct biological consequences of these two states. This study aims to resolve the prognostic discordance between genomic subgroups in the context of modern therapeutic interventions. Methods: We conducted a comparative meta-analysis of nine pivotal studies comprising 4,125 patients, selected through a stringent protocol requiring paired cytogenetic (FISH) and molecular sequencing data. Patients were stratified into three genomic subgroups: Wild type, monoallelic disruption (isolated deletion or isolated mutation), and biallelic disruption (deletion plus mutation). Data were synthesized using a random-effects model to calculate pooled hazard ratios (HR) for Overall Survival (OS), with specific subgroup analyses performed for Plasma Cell versus Lymphoid malignancies to account for lineage heterogeneity. Results: The analysis revealed a profound prognostic dichotomy. In Multiple Myeloma, biallelic inactivation conferred a catastrophic prognosis with a pooled hazard ratio for death of 3.82 compared to Wild Type. Conversely, isolated del(17p) carried a significantly lower risk (HR 1.82), suggesting functional compensation by the residual allele. In CLL and Waldenström's Macroglobulinemia, TP53 mutations acted as independent drivers of poor survival (HR 2.80) even in the absence of deletion, consistent with a dominant-negative mechanism. The double hit phenotype was consistently associated with a median survival reduction exceeding fifty percent compared to monoallelic cases across all lineages. Conclusion: The prognostic weight of TP53 abnormalities is defined by allelic dosage. Biallelic inactivation represents a distinct, high-risk biological entity requiring novel therapeutic approaches, whereas monoallelic alterations often exhibit intermediate outcomes. Clinical guidelines must mandate sequencing alongside FISH to prevent misstratification and overtreatment.